2020
DOI: 10.1096/fj.202000657r
|View full text |Cite
|
Sign up to set email alerts
|

Fine particulate matter inhibits phagocytosis of macrophages by disturbing autophagy

Abstract: Mounting evidence from epidemiological and clinical studies has revealed marked correlations between the air pollutant fine particulate matter (FPM) and respiratory diseases. FPM reaches distal airways and deposits in alveolar regions where it can act directly on alveolar macrophages. However, the detailed effect of FPM on the physiological function of alveolar macrophages and the underlying mechanisms remain unclear. In this study, we showed that exposing THP-1-derived macrophages to FPM led to autophagy dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Another possibility is the over activation of phosphoinositide 3-kinase delta isoform (PI3Kδ), which inhibits Ras homologue family member A activity, also implicated in actin polymerization . SOA could inhibit lysosomal maturation which is required in phagocytosis. , Other alterations mediated by these particles could involve: a decrease of interferon-gamma (IFNγ) and interferon-β during the immune defense against viral infection; and a decrease of natural killer (NK) cell recruitment into the airway after S. aureus infection that may be explained by CCL5 and IFNγ diminution, , as they play an important role in proliferation and accumulation of NK cells. , Whether SOA mediates the above mechanisms and its associated immune function alterations warrants further studies.…”
Section: Pathogenic Impact Of Soamentioning
confidence: 99%
“…Another possibility is the over activation of phosphoinositide 3-kinase delta isoform (PI3Kδ), which inhibits Ras homologue family member A activity, also implicated in actin polymerization . SOA could inhibit lysosomal maturation which is required in phagocytosis. , Other alterations mediated by these particles could involve: a decrease of interferon-gamma (IFNγ) and interferon-β during the immune defense against viral infection; and a decrease of natural killer (NK) cell recruitment into the airway after S. aureus infection that may be explained by CCL5 and IFNγ diminution, , as they play an important role in proliferation and accumulation of NK cells. , Whether SOA mediates the above mechanisms and its associated immune function alterations warrants further studies.…”
Section: Pathogenic Impact Of Soamentioning
confidence: 99%
“…39,51 ROS induced by fine particulate matter destroyed the acidic microenvironment of lysosome and impaired lysosomal proteolytic activity. 67 Significantly, treatment of antioxidants (n-acetylcysteine) not only restored lysosomal acidity but also released the flux blockade. 136 Therefore, above studies indicated that oxidative stress-mediated cell homeostasis disruption mediates incomplete autophagy in different types of cells.…”
Section: Oxidative Stressmentioning
confidence: 98%
“…Studies have shown that cationic liposomes and rotenone‐induced excessive ROS production, which lead to lysosome membrane permeabilization and incomplete autophagy 39,51 . ROS induced by fine particulate matter destroyed the acidic microenvironment of lysosome and impaired lysosomal proteolytic activity 67 . Significantly, treatment of antioxidants (n‐acetylcysteine) not only restored lysosomal acidity but also released the flux blockade 136 .…”
Section: Signaling Molecules and Pathways Regulating Incomplete Autop...mentioning
confidence: 99%
“…In a cross-sectional study in healthy children, the carbon content of airway macrophages was inversely associated with lung function status [ 56 ]. In addition, previous studies revealed that exposure to PM resulted in decreased macrophage phagocytosis in both murine and human models [ 50 , 57 , 58 , 59 ]. PM2.5 exposure to pneumococcus-infected mice led to macrophage dysfunctions, including impairing phagocytosis with nitric oxide production; in addition, decreased bacterial clearance activity via dampened proinflammatory cytokine expression was also observed.…”
Section: Initial Process Reactions After Introducing Particulate Matt...mentioning
confidence: 99%
“…Exposure to fine PM (FPM) in human macrophages could inhibit phagocytosis by promoting the expression of autophagy-related 2A (ATG2A) and reactive oxygen species generation via the extracellular signal-regulated kinase 1/2 (ERK1/2) signaling pathway, which leads to further autophagy dysfunction. Moreover, FPM compromised the phagocytic ability of macrophages on Escherichia coli and apoptotic neutrophils [ 59 ].…”
Section: Initial Process Reactions After Introducing Particulate Matt...mentioning
confidence: 99%